1988
DOI: 10.1159/000210753
|View full text |Cite
|
Sign up to set email alerts
|

Ciclosporin Inhibits Phorbol-Ester-Induced Hyperplastic Transformation and Tumor Promotion in Mouse Skin Probably by Suppression of Ca<sup>2+</sup>/Calmodulin-Dependent Processes such as Phosphorylation of Elongation Factor 2

Abstract: This study deals with the mechanism of the inhibitory effect exerted by the immunosuppressant ciclosporin (CsA) on phorbol-ester-induced inflammation, epidermal hyperplasia and tumor promotion in mouse skin in vivo. This effect coincides with an inhibition of the phosphorylation of a 100-kilodalton protein (p 100) in epidermal cytosol in vitro, which has been identified as elongation factor 2 (EF-2) of protein biosynthesis. Phosphorylation of EF-2 is dependent on Ca2+ and calmodulin, and inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Calcium elevation or influx increases eEF2 phosphorylation through activation of eEF2 kinase (Marin et al,1997; Iizuka et al,2007; Chen et al,2009). Because the eEF2 phosphorylation system has a rapid turnover rate (Gschwendt et al,1988; Arora et al,2005), the level of p‐eEF2 in a cell is largely controlled by the activity of eEF2 kinase. In chick NM, afferent deprivation leads to a rapid increase in the basal level of intracellular calcium concentration (Zirpel et al,1995a, b; Zirpel and Rubel,1996), which presumably should activate eEF2 kinase and thus enhance eEF2 phosphorylation, which is the opposite of what we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium elevation or influx increases eEF2 phosphorylation through activation of eEF2 kinase (Marin et al,1997; Iizuka et al,2007; Chen et al,2009). Because the eEF2 phosphorylation system has a rapid turnover rate (Gschwendt et al,1988; Arora et al,2005), the level of p‐eEF2 in a cell is largely controlled by the activity of eEF2 kinase. In chick NM, afferent deprivation leads to a rapid increase in the basal level of intracellular calcium concentration (Zirpel et al,1995a, b; Zirpel and Rubel,1996), which presumably should activate eEF2 kinase and thus enhance eEF2 phosphorylation, which is the opposite of what we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium elevation or influx increases eEF2 phosphorylation through activation of eEF2 kinase (Marin et al, 1997; Iizuka et al, 2007; Chen et al, 2009). Since the eEF2 phosphorylation system has a rapid turnover rate (Gschwendt et al, 1988; Arora et al, 2005), the level of p-eEF2 in a cell is largely controlled by the activity of eEF2 kinase. In chick NM, afferent deprivation leads to a rapid increase in the basal level of intracellular calcium concentration (Zirpel et al, 1995a; b; Zirpel and Rubel, 1996), which presumably should activate eEF2 kinase and thus enhance eEF2 phosphorylation, opposite to what we observed.…”
Section: Discussionmentioning
confidence: 99%
“…In kératinocytes the only direct evidence for a CsA-calmodulin interaction is from work by Gschwendt et al [28,29]. They have found that treatment of mouse kératinocytes with CsA in vitro inhibits phorbol esterinduced phosphorylation of elongation fac tor 2.…”
Section: Discussionmentioning
confidence: 99%